Treatment decision‐making during outpatient clinic visit of patients with esophagogastric cancer. The perspectives of clinicians and patients, a mixed method, multiple case study. (15th February 2022) - Luijten, Josianne C. H. B. M.; Brom, Linda; Vissers, Pauline A. J.; van de Wouw, Yes. A. J.; Warmerdam, Fabienne A. R. M.; Heisterkamp, Joos; Mook, Stella; Oulad Hadj, Jamal; van Det, Marc J.; Timmermans, Liesbeth; Hulshof, Maarten C. C. M.; van Laarhoven, Hanneke W. M.; et al.
Abstract: Background: The probability of undergoing treatment with curative intent according to the hospital of diagnosis varies for esophagogastric cancer in the Netherlands. Little is known about the factors contributing to this variation. This study aimed to improve the understanding of the differences between the multidisciplinary team meeting treatment proposal and the treatment that was actually carried out and to qualitatively investigate the differences in treatment decision‐making after the multidisciplinary team meeting treatment proposal between hospitals. Methods: To gain an in‐depth understanding of treatment decision‐making, quantitative data (i.e., multidisciplinary team meeting proposal and treatment that was carried out) were collected from the Netherlands Cancer Registry. Changes in the multidisciplinary team meeting proposal and applied treatment comprised changes in the type of treatment option (i.e., curative or palliative, or no change) and were calculated according to the multivariable multilevel probability of undergoing treatment with curative intent (low, middle, and high). Qualitative data were collected from eight hospitals, including observations of 26 outpatient clinic consultations, 30 in‐depth interviews with clinicians, seven focus groups with clinicians, and three focus groups with patients. Clinicians and patients' perspectives were assessed using thematic content analysis. Results: The multidisciplinary team meeting proposal and applied treatment were concordant in 97% of the cases. Clinicians' implementation of treatment decision‐making in clinical practice varied, which was mentioned by the clinicians to be due to the clinician's personality and values. Differences between clinicians consisted of discussing all treatment options versus only the best fitting treatment option and the extent of discussing the benefits and harms. Most patients aimed to undergo curative treatment regardless of the consequences, since they believed this could prolong their life. Conclusion: Since changes in the multidisciplinary team meeting‐proposed treatment and actual treatment were rarely observed, this study emphasizes the importance of an adequately formulated multidisciplinary team meeting proposal. Abstract : The probability of undergoing treatment with curative intent according to the hospital of diagnosis has been shown to vary considerably for esophagogastric cancer in the Netherlands. Little is known about the factors that contribute to this variation in practice. In this study, we aimed to improve our understanding of the differences between the multidisciplinary team meeting (MDTM) treatment proposal and the treatment that was actually carried out and to qualitatively investigate the differences in treatment decision‐making (TDM) after the MDTM treatment proposal between hospitals.